Stakeholder Engagement as a Core Management Function: Analysing the Business Value of Stakeholder Engagement for Nigerian Business Organizations - Isike, Christopher; Ajeh, Alice (Journal of Economics and Behavioral Studies, 2017)
This article examines the importance of adopting credible stakeholder engagement (SE) as a core management function, with particular reference to Nigerian business organizations. It used content analysis method to specifically examine the role of SE in business organizations; determine the utility of credible SE as a core management function rather than as an add-on; and trace measurable links between SE and business value (profit) with reference to selected multinational companies operating in Nigeria’s Niger Delta region. The article situated its arguments within the Stakeholder Model of Business Value Creation, which it used as a conceptual analytical framework to justify why business organizations in the region should dedicate more attention and resources to quality SE for sustainable profitability. As the findings show, business organizations in the Niger Delta tend to treat SE as an add-on rather than as a core management function. Therefore, given the business value that effective SE adds to an organization, a paradigm shift is required. Business organizations in Nigeria should elevate SE to core management level with the requisite budget to make it fully functional.